Food insecurity and mental health of college students in Lebanon: a cross-sectional study. (23rd August 2022) - Itani, Rita; Mattar, Lama; Kharroubi, Samer; Bosqui, Tania; Diab-El-Harake, Marwa; Jomaa, Lamis
Abstract: The present study aimed to assess the prevalence of food insecurity (FI) among college students and explore its association with indicators of mental and psychosocial health. Data were collected using a cross-sectional online survey from college students in different universities in Lebanon during the Spring 2021 semester. FI was assessed using the validated eight-item food insecurity experience scale. The mental health of college students was assessed using validated screening tools for depression, anxiety and well-being, namely the Patient Health Questionnaire (PHQ-9), the General Anxiety Disorder-7 (GAD-7) and the World Health Organization (WHO-5) index, respectively. Multiple linear regression models were conducted to assess the relationship of FI with PHQ-9, GAD-7 and WHO-5 scores. A total of 745 students completed the online survey. Approximately 39 % of students in the sample were experiencing FI of which 27·4, 8·1, and 3·5 % were experiencing mild, moderate and severe FI, respectively. Low maternal education, low household monthly income and high levels of stress were significant correlates of FI among college students ( P -trend < 0·001). In addition, 22·6 and 34·4 % of students showed severe symptoms of depression and anxiety, respectively. Regression models showed that FI was associated with higher scores on PHQ-9 and GAD-7 ( β = 2·45; 95 % CI [1·41, 3·49]) and ( β = 1·4; 95 % CI [1·1, 2·2], respectively) and lower scores on WHO-5 ( β = −4·84; 95 % CI [−8·2, −1·5]). In conclusion, a remarkable proportion of college students reported experiencing different forms of FI, which was associated with poorer mental health and well-being outcomes. Public health programmes and interventions are needed to mitigate FI and improve student health-related outcomes.